2023
DOI: 10.1371/journal.pone.0285027
|View full text |Cite
|
Sign up to set email alerts
|

For whom does it pay to be a moral capitalist? Sustainability of corporate financial performance of ESG investment

Abstract: This paper analyzes the risk-return characteristics of socially responsible investing by employing a time-varying capital gain and Sharpe ratio analysis for various investment horizons. We employ the MSCI ESG (environmental, social and governance) leaders indices in ten markets encompassing Australia, Canada, Europe, Japan, UK, USA, China, India, Russia, and South Africa. Our sample ranges from 2007–2020. We document that ESG investments have very desirable return and hedging attributes for investors in these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The potential effect of SPP of PPP projects on corporate ESG performance may be more pressing for study given the magnitude of PPP projects and their social, environmental, economic and political significance in an economy. Last but not least, relevant studies could also be conducted in different countries, especially between developing and developed countries, given that they have assumed common but differentiated emphasis on the ESG evaluation system [ 88 ].…”
Section: Discussion Conclusion Implication and Future Researchmentioning
confidence: 99%
“…The potential effect of SPP of PPP projects on corporate ESG performance may be more pressing for study given the magnitude of PPP projects and their social, environmental, economic and political significance in an economy. Last but not least, relevant studies could also be conducted in different countries, especially between developing and developed countries, given that they have assumed common but differentiated emphasis on the ESG evaluation system [ 88 ].…”
Section: Discussion Conclusion Implication and Future Researchmentioning
confidence: 99%
“…Studies have also shown an exciting point: the return on ESG-related investment is correlated with the stability of society and the economy. Studies show that the higher the degree of stableness of the society and economy investors, the lower the degree of return from the ESG-related investment they would expect [11,12]. Studies are mainly based on the effect of the COVID-19 pandemic, assuming societies and economies are unstable during the pandemic, which also implies that the current ESGrelated investment will have less expected return.…”
Section: Literature Reviewmentioning
confidence: 99%